2008
DOI: 10.1161/hypertensionaha.107.096248
|View full text |Cite|
|
Sign up to set email alerts
|

History of Fetal Growth Restriction Is More Strongly Associated With Severe Rather Than Milder Pregnancy-Induced Hypertension

Abstract: Abstract-We assessed whether fetal growth restriction without pregnancy-induced hypertension (PIH) is associated with the different clinical subgroups of PIH in the subsequent pregnancy. We also assessed the maternal and paternal contributions to this effect. Pairs of first and second, second and third, third and fourth, and fourth and fifth births were identified among all of the births in Norway: 137 375 pairs with same mother and father, 18 376 pairs with same mother and different fathers, and 18 916 pairs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
15
0
3

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 37 publications
6
15
0
3
Order By: Relevance
“…The newborn's birth measurements from the Mild PE were 48.67±1.33 cm and for the group SP 46.42±2.36 vs. neonates from normotensive pregnancies (50.65±1.2cm; p<0.05). Also, these results, too, are same as from the associated literature in this area [5,7,14,15].…”
Section: Fetal Growth and Body Proportion During Pre-eclamptic Pregnasupporting
confidence: 86%
See 2 more Smart Citations
“…The newborn's birth measurements from the Mild PE were 48.67±1.33 cm and for the group SP 46.42±2.36 vs. neonates from normotensive pregnancies (50.65±1.2cm; p<0.05). Also, these results, too, are same as from the associated literature in this area [5,7,14,15].…”
Section: Fetal Growth and Body Proportion During Pre-eclamptic Pregnasupporting
confidence: 86%
“…The US made every obstetrician's dream comes true, opening a window in the intra-uterine content,allowing fetus growth and development observation, as well as examining the placenta and determining the amount of amniotic fluid; and all of that is safe, direct, intentional and repeatable. Fetal growth measured with US with other risk factors could predict development of PE and poor neonatal outcomes [7,8].…”
Section: Fetal Growth and Body Proportion During Pre-eclamptic Pregnamentioning
confidence: 99%
See 1 more Smart Citation
“…It has been postulated that the mild late-onset form of preeclampsia is etiologically different from the severe early onset form (19,20). Whereas mild preeclampsia at term may represent a hypertensive response to minimally impaired (or perhaps even normal) perfusion of the placenta in highly sensitive or predisposed women, the severe disease could be the physiologic reaction of any mother due to profoundly reduced placental perfusion.…”
Section: Discussionmentioning
confidence: 99%
“…They also provide data that support but also some that argue against the concept that the pregnancy complication, preeclampsia, may be more than one disease. 1 In previous studies these authors demonstrated that women who have had a growth-restricted infant without preeclampsia are more likely to have preeclampsia in a subsequent pregnancy. 2 Those data and similar findings in the current study support pathological findings indicating the similarity of IUGR and preeclampsia.…”
mentioning
confidence: 98%